"Catching butterflies": Marion Milner and stream of consciousness writing. Issue 6 (17th June 2020) - Tyson, Helen
Abstract: This article explores the use of stream of consciousness writing in the early work of the British psychoanalyst, life writer, and artist, Marion Milner. Focusing on Milner's 1934 book, A Life of One's Own (first published under the pen name Joanna Field), the first part of the article situates Milner's use of stream of consciousness writing alongside the work of her contemporaries Virginia Woolf, May Sinclair, and Dorothy Richardson. Building on Vanessa Smith's recent archival work on Milner's reading of Woolf, this article provides further insight into previously unpublished archival material that reveals Milner explicitly identifying her "method" with that of T. S. Eliot in The Waste Land and commenting on Dorothy Richardson's rejection of the "omniscient observer" while she worked on A Life of One's Own . Reading A Life of One's Own alongside the writing of Milner's modernist contemporaries, I argue not only that Milner's writing contains striking formal and thematic echoes of modernist stream of consciousness prose but also that she uses forms of free writing as the basis for her own distinctive experiment in disentangling her own wants and desires from those manufactured by the forces of patriarchal capitalist modernity. The second part of the article demonstrates how Milner's experiments with stream of consciousness writing became, in the political context of the 1930s, fraught with an uncertainty about the boundaries of the individual mind. Examining Milner's anxieties about the forms of personal surrender solicited by modernist artworks, I show how Milner's own experiments with stream of consciousness writing became, increasingly in the 1930s, part of an experiment in trying to extricate the individual from the rising currents of fascism. Tracking Milner's, Richardson's, and Woolf's dramatisation of the pleasures and perils of aesthetic abandon, I argue that, although Milner struggles to negotiate her own immersion within the rising sociopolitical currents of history, the significance of her writing lies not only in the vividness with which it dramatises this fragile encounter but also in the argument that it makes for the value of creative and critical processes in an age of fascism.